2023
DOI: 10.1111/bpa.13135
|View full text |Cite
|
Sign up to set email alerts
|

Studying the imaging features and infarction mechanism of vertebrobasilar dolichoectasia with high‐resolution magnetic resonance imaging

Abstract: The mechanisms underlying ischemic infarction in patients with vertebrobasilar dolichoectasia (VBD) remain unclear. In this study, we retrospectively analyzed the imaging characteristics of high‐resolution magnetic resonance imaging (HR‐MRI) in patients with VBD to explore the possible mechanisms of ischemic stroke (IS) in patients with VBD. Patients with VBD were recruited from the HR‐MRI database between July 2017 and June 2021. HR‐MRI was used to evaluate the diameter, bifurcation height, laterality, arteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Vertebrobasilar dolichoectasia is characterized by pronounced dilatation, extension, tortuosity, or angulation of the vertebrobasilar artery, attributed to a range of diverse factors (137). Its pathogenesis is multifactorial, encompassing atherosclerosis, hypertension, developmental anomalies, and additional elements including infection (138).…”
Section: Geometric Parameters Of the Arterymentioning
confidence: 99%
See 1 more Smart Citation
“…Vertebrobasilar dolichoectasia is characterized by pronounced dilatation, extension, tortuosity, or angulation of the vertebrobasilar artery, attributed to a range of diverse factors (137). Its pathogenesis is multifactorial, encompassing atherosclerosis, hypertension, developmental anomalies, and additional elements including infection (138).…”
Section: Geometric Parameters Of the Arterymentioning
confidence: 99%
“…An augmentation in both the mean diameter and bifurcation height of the BA is firmly linked to the likelihood of a stroke occurrence. Excessive bifurcation angles tend to impose pulling and twisting forces on the perforating arteries of the BA, resulting in diminished blood flow (137,140). Meanwhile, the widening of the BA diameter leads to a noteworthy reduction in blood flow velocity, thereby fostering the development of microemboli and subsequent lipid deposition.…”
Section: Geometric Parameters Of the Arterymentioning
confidence: 99%
“…Mortality rates are high due to the non‐specific symptoms and delay in diagnosis. Here, Tao et al (2023), used high‐resolution MRI (HR‐MRI), to fully characterise the arterial structure and function in 24 patients and concluded that risk of stroke was associated with bifurcation height and arterial turbulence and inferior diameters [ 10 ]. This work should help to enable more effective stratified risk assessment following larger‐scale clinical studies.…”
mentioning
confidence: 99%
“…Vertebrobasilar dolichoectasia is a progressive and complex cerebral artery disease characterized by abnormal elongation, dilation, and distortion of vertebrobasilar arteries of unknown pathogenesis. 1,2 Thrombus in vertebrobasilar dolichoectasia may consist of both fresh and old components, and the extension can occur within hours, requiring a more aggressive management. Acute thrombosis can be treated with intravenous thrombolysis or thrombectomy for occlusive thrombus, but the efficacy remains uncertain.…”
mentioning
confidence: 99%